Historical aspects of using of biodegradable magnesium-based alloys for osteosynthesis (literature review) - Chorny, Vadim; Yatsun, Yevgeniy; Golovakha, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
History of creation of the devices for osteosynthesis of fractures has gone more than 150-year way of testing of a variety of metal alloys, development and improvement of metal fixation implants. To date, stainless steel and titanium alloys are the main materials used for the manufacturing of internal implants. But existing mismatch in mechanical properties between the material and the bone tissue particularly in elastic modulus can cause stress fractures, bone tissue resorption around the implant and its migration as a result. Applying in 316L alloy such dopant as nickel may lead to various inflammatory and allergic reactions. Feature of metallic magnesium to dissolve in tissues of a living organism has been known since the beginning of the 20th century. Payr suggested to use needles made of this material for the treatment of angiomas in order to achieve thrombosis of vessels surrounding tumor. They started further to apply magnesium and magnesium-based alloys in vessel surgery as stents. At the end of 1990th experiments on creation of biodegradable implants for osteosynthesis based on magnesium alloys were renewed owning to good combination of their mechanical, electro-chemical and biological properties. Histological and cytological studies have shown no adverse effects on magnesium ions to osteogenesis. Some researchers have discovered their beneficial effect on bone formation. After studies of toxic effects of degradation products of magnesium alloy with zinc, manganese and niobium there were not revealed any significant differences in the biochemical parameters of blood and urine comparing to control groups of animals. Laboratory studies of possible mutagenic effect and possible DNA lesions showed an absence of any negative impact of magnesium ions on the DNA of human lymphocytes. As an analysis of the professional literature over the past 10 years shows that the number of scientific articles on studying of the properties of biodegradable magnesium-based alloys, their effects on bone formation as well as their use in osteosynthesis has significantly increased. But such studies they perform mainly abroad. Topicality of the problem highlights a number of issues need to be addressed: 1) uncertain mechanism of impact of alloys degradation products on bone tissue, surrounding soft tissues and osteogenesis; 2) not fully not explored the impact of toxic effects of alloy products resolution on the human organism; 3) high rate of known magnesium-based alloys resolution inhibiting an opportunity to provide the period of stabile fixation of fracture for normal healing.